Learn more about

Refine search

Results (displaying matches 1-50 of 88) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
169.a.169.1 169.a \(y^2 + (x^3 + x + 1)y = x^5 + x^4\) $E_6$ 0
196.a.21952.1 196.a \(y^2 + (x^2 + x)y = x^6 + 3x^5 + 6x^4 + 7x^3 + 6x^2 + 3x + 1\) $E_1$ 0
324.a.648.1 324.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^4 + 2x^3 + x^2\) $E_3$ 0
676.b.17576.1 676.b \(y^2 + (x^2 + x)y = -x^6 + 3x^5 - 6x^4 + 6x^3 - 6x^2 + 3x - 1\) $E_1$ 0
784.c.614656.1 784.c \(y^2 = x^5 - 4x^4 - 13x^3 - 9x^2 - x\) $E_3$ 0
1296.a.20736.1 1296.a \(y^2 = x^5 - x^4 - 3x^3 + 4x^2 - x\) $E_3$ 0
2187.a.6561.1 2187.a \(y^2 + (x^3 + 1)y = -1\) $J(E_3)$ 0
2704.a.43264.1 2704.a \(y^2 = x^5 - 5x^3 - 5x^2 - x\) $E_6$ 0
2916.a.5832.1 2916.a \(y^2 + (x^3 + 1)y = x^3\) $J(E_1)$ 0
3721.a.3721.1 3721.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 + 3x^2 + x\) $E_6$ 2
3969.b.35721.1 3969.b \(y^2 + (x^3 + x + 1)y = -2x^5 + 3x^4 - 3x^2\) $E_6$ 2
3969.c.35721.1 3969.c \(y^2 + (x^2 + x)y = x^5 - 5x^4 + 4x^3 - x\) $E_6$ 0
5184.a.46656.1 5184.a \(y^2 + x^3y = x^3 + 2\) $J(C_2)$ 0
6075.a.18225.1 6075.a \(y^2 + (x^3 + 1)y = x^3 + 1\) $J(E_6)$ 0
8281.b.405769.1 8281.b \(y^2 + (x^3 + x + 1)y = -3x^5 + 9x^4 - 7x^3 - 2x^2 + x\) $E_6$ 2
8281.c.405769.1 8281.c \(y^2 + (x^2 + x)y = x^5 + 8x^4 + 11x^3 + 3x^2 - x\) $E_6$ 0
8649.b.700569.1 8649.b \(y^2 + (x^2 + x)y = 9x^5 + 2x^4 - 21x^3 - 22x^2 - 8x - 1\) $E_6$ 0
8649.c.700569.1 8649.c \(y^2 + (x^2 + x)y = x^5 + 9x^4 + 13x^3 + 4x^2 - x\) $E_6$ 0
11881.a.11881.1 11881.a \(y^2 + (x^2 + x)y = x^5 - 3x^4 + 2x^2 - x\) $E_6$ 0
12321.a.36963.1 12321.a \(y^2 + (x^3 + x + 1)y = x^5 + 3x^4 + 4x^3 + 2x^2\) $E_6$ 2
12544.a.12544.1 12544.a \(y^2 = x^5 + 2x^4 - x^3 - 3x^2 - x\) $E_6$ 0
12544.c.12544.1 12544.c \(y^2 = x^5 - 2x^4 - x^3 + 3x^2 - x\) $E_6$ 0
12544.i.614656.1 12544.i \(y^2 = x^5 + 4x^4 - 13x^3 + 9x^2 - x\) $E_3$ 0
13689.a.13689.1 13689.a \(y^2 + (x^3 + x + 1)y = x^5 - x^4 - 4x^3 - 2x^2\) $E_6$ 2
13689.b.13689.1 13689.b \(y^2 + (x^2 + x)y = x^5 + 3x^4 + x^3 - 2x^2 - x\) $E_6$ 0
15552.c.746496.1 15552.c \(y^2 + x^3y = 3x^3 + 8\) $J(E_6)$ 0
15876.b.222264.1 15876.b \(y^2 + (x^3 + x + 1)y = -x^6 + 2x^5 - 4x^4 + 4x^3 - 5x^2 + 2x - 1\) $E_3$ 0
17689.a.17689.1 17689.a \(y^2 + (x^2 + x)y = x^5 - 4x^4 + 2x^3 + x^2 - x\) $E_6$ 0
17689.b.17689.1 17689.b \(y^2 + (x^3 + x + 1)y = -3x^4 - 3x^3 + x^2 + x\) $E_6$ 2
18225.a.18225.1 18225.a \(y^2 + (x^3 + 1)y = 1\) $J(E_6)$ 1
20736.a.20736.1 20736.a \(y^2 = x^5 + x^4 - 3x^3 - 4x^2 - x\) $E_3$ 0
20736.f.186624.1 20736.f \(y^2 = x^5 - 2x^4 - 9x^3 - 7x^2 - x\) $E_6$ 0
20736.g.186624.1 20736.g \(y^2 = x^5 + 2x^4 - 9x^3 + 7x^2 - x\) $E_6$ 0
21316.a.42632.1 21316.a \(y^2 + (x^3 + x + 1)y = 3x^3 + 4x^2 + x\) $E_6$ 2
21904.e.350464.1 21904.e \(y^2 = x^5 + 3x^4 - 11x^3 + 8x^2 - x\) $E_6$ 0
24649.a.24649.1 24649.a \(y^2 + (x^2 + x)y = x^5 + 4x^4 + 3x^3 - x^2 - x\) $E_6$ 0
26244.c.157464.1 26244.c \(y^2 + (x^3 + 1)y = 2x^3\) $J(E_1)$ 0
26244.d.314928.1 26244.d \(y^2 + y = x^6 - 2x^3\) $J(E_3)$ 1
26244.e.472392.1 26244.e \(y^2 + (x^3 + 1)y = 2\) $J(E_3)$ 0
32761.a.32761.1 32761.a \(y^2 + (x^3 + x + 1)y = x^5 + 10x^2 + 19x + 10\) $E_6$ 2
37636.a.602176.1 37636.a \(y^2 + (x^3 + x + 1)y = x^5 + 4x^4 + 6x^3 + 3x^2\) $E_6$ 2
38416.a.614656.1 38416.a \(y^2 = x^6 - 3x^5 - x^4 + 7x^3 - x^2 - 3x + 1\) $E_1$ 2
43264.c.43264.1 43264.c \(y^2 = x^5 - 5x^3 + 5x^2 - x\) $E_6$ 0
46656.c.93312.1 46656.c \(y^2 + x^3y = x^3 - 1\) $J(E_6)$ 1
48841.b.830297.1 48841.b \(y^2 + (x^3 + x + 1)y = -x^6 + 2x^5 - 5x^4 + 6x^3 - 6x^2 + 2x - 1\) $E_6$ 0
52441.a.52441.1 52441.a \(y^2 + (x^2 + x)y = x^5 + 5x^4 + 5x^3 - x\) $E_6$ 0
59049.a.177147.1 59049.a \(y^2 + (x^3 + 1)y = x^3 - 1\) $J(E_3)$ 1
62208.n.746496.1 62208.n \(y^2 = x^6 - 3x^3 + 2\) $J(E_6)$ 0
72900.a.291600.1 72900.a \(y^2 + y = x^6 - 2x^3 + 1\) $J(E_6)$ 1
72900.b.291600.1 72900.b \(y^2 + x^3y = 2x^3 + 5\) $J(E_6)$ 0
Next

Download all search results for